Male infant patient with a mesenteric cyst in the greater and lesser omenta: A case report (2020)
Background Mesenteric cysts are intra-abdominal masses of congenital origin, which most frequently occur in children, with an incidence of approximately 1 case per 20,000 pediatric admissions. Its progression can be asymptomatic, and its diagnosis can be incidental. However, it usually occurs with symptoms such as nausea, vomiting, constipation, sensation of a mass, and/or diarrhea. The diagnostic imaging method of choice is abdominal ultrasound. Case presentation Below, we present the case of a previously healthy 1-year-old male patient with nonspecific symptoms, who was referred to a tertiary hospital. The presence of a mesenteric cyst was detected at the end of the diagnostic approach. Conclusion It is important to know these pathologies even though they are infrequent, because although they are benign masses by definition, they can lead to complications such as intestinal torsion, intestinal obstruction, and even peritonitis.